2014
DOI: 10.1039/c4an00153b
|View full text |Cite
|
Sign up to set email alerts
|

Dual-stimuli responsive i-motif/nanoflares for sensing ATP in lysosomes

Abstract: A dual-stimuli responsive i-motif/nanoflare for molecule detection in lysosomes was designed. By combining the structure-switchable i-motif sequence and high recognition ability of an adenosine triphosphate (ATP) aptamer, subcellular sensing and visualization sensing of ATP in lysosomes at the subcellular level can be achieved. This general sensing technique can be applied for a broad range of cellular communication studies to improve our understanding of subcellular signaling and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Similarly, cyclic voltammetric detection of Cr(III) ions was also carried out for Cr(III) concentration ranging from 5x10 À4 M to 1.5x10 À2 M, using the microbe modified CPE in the pH range of 2 to 4. From the voltammograms portrayed in Figs.4(a-c) using the Cf-CPE at pH 2, 3 and 4 respectively, the LLOD for Cr(III) ions is found to be 5x10 À4 M. The slight shifts in the cathodic peak potentials observed as a function of Cr(VI) concentration, at different proton concentration/pH, has also been reported by other workers [35,[38][39][40].…”
Section: Cyclic Voltammetric Analysis Of Cr(vi)/cr(iii) Ions Using Cfsupporting
confidence: 82%
“…Similarly, cyclic voltammetric detection of Cr(III) ions was also carried out for Cr(III) concentration ranging from 5x10 À4 M to 1.5x10 À2 M, using the microbe modified CPE in the pH range of 2 to 4. From the voltammograms portrayed in Figs.4(a-c) using the Cf-CPE at pH 2, 3 and 4 respectively, the LLOD for Cr(III) ions is found to be 5x10 À4 M. The slight shifts in the cathodic peak potentials observed as a function of Cr(VI) concentration, at different proton concentration/pH, has also been reported by other workers [35,[38][39][40].…”
Section: Cyclic Voltammetric Analysis Of Cr(vi)/cr(iii) Ions Using Cfsupporting
confidence: 82%
“…Among various noble metal nanomaterials, gold nanomaterials are most intensely investigated as imaging contrast agents and nanocarriers . As a result, the integration of aptamer with gold nanomaterials, such as Au nanorods (AuNRs), Au nanoparticles, Au nanocages, Au nanostars (AuNSs), hollow gold nanospheres (HAuNS), and Au nanoclusters (Au NCs), has been widely employed in in vivo applications in diverse areas, such as intracellular molecular imaging, cancer cell and tumor imaging, targeted delivery of therapeutic cargos (e.g., anticancer drug, protein, and gene), and cancer therapy . In one example, Huang et al demonstrated the use of AuNRs as an efficient and robust multivalent platform for molecular assembly of aptamers for targeted cell imaging .…”
Section: Molecular Engineering Of Aptamer‐based Nanomaterials Toward mentioning
confidence: 99%
“…In addition to targeted cell imaging, aptamer‐based gold nanomaterials have also been used for intracellular molecular imaging. For instance, by combining the structure‐switching i‐motif and the highly selective adenosine triphosphate (ATP) aptamer, Jin et al developed a dual‐stimuli responsive i‐motif/nanoflares for ATP imaging in lysosomes . Later, Chen et al (Figure B) reported the use of polyA‐based SNA aptamer nanobeacons (PAaptNBs) that are functionalized with rationally designed polyadenine (polyA) diblock oligonucleotides through they achieved programmable engineering of PAaptNB for intracellular ATP imaging.…”
Section: Molecular Engineering Of Aptamer‐based Nanomaterials Toward mentioning
confidence: 99%
“…Their sensor enabled localization of both nucleotides, but not quantification (Wang Y. et al, 2013 ). Along the same lines, a multitude of sensing techniques was developed for the fluorescent detection of ATP in living cells in general (Tan et al, 2012 ; Wu C. et al, 2013 ; Liu et al, 2014 ; Jia et al, 2015 ; Qiang et al, 2015 ; Wang W. et al, 2015 ) and in lysosomes specifically (Jin et al, 2014 ). Yi et al went a step further and used the deeper penetration depth of two-photon microscopy to visualize ATP in zebrafish (Yi et al, 2014 ).…”
Section: Small Molecule Aptasensorsmentioning
confidence: 99%